Experimental Study of Exhaust Manifold Modification using Orifice on Suzuki Satria F 150 - Sartono Putro; Auliya Imam Maulana; Ribut Wahyu Purwanto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of modification of Exhaust Manifold using orifice on engine performance of Suzuki Satria F 150. Experiments were carried out by installing orifice blinds with diameters of 18, 20, 22 mm and circular perforated orifices with diameters of 19, 19.5, 20.5, and 20. mm on the exhaust manifold. Engine performance, torque and power were tested with dyno test. Fuel consumption is measured using a measuring tube. The results showed that using an orifice blind modification, the smaller the exhaust manifold area, the smaller the torque and power produced. The modification uses an orifice hole, the torque and power produced are close to the standard exhaust manifold. Optimal sfc on modifications using orifice blinds is obtained at engine speed of 6000 to 8500 rpm. While at engine speed of 9000 rpm and above, the modification of the exhaust manifold orifice hole is more optimal.